Effects of sports injury prevention training on the biomechanical risk factors of anterior cruciate ligament injury in high school female basketball players - Lim, B.-O.; Lee, Y. S.; Kim, J. G.; An, K. O.; Yoo, J.; Kwon, Y. K. (The American Journal of Sports Medicine, 2009)
Background Female athletes have a higher risk of anterior cruciate ligament injury than their male counterparts who play at similar levels in sports involving pivoting and landing.